Effect of Orexin-A on Cortisol Secretion in H295R Cells via p70S6K/4EBP1 Signaling Pathway - Xiaocen Chang; Yuyan Zhao; Lei Guo (International Journal of Endocrinology)
Orexin-A is a neuropeptide that orchestrates diverse central and peripheral processes. It is now clear that orexin system plays a central role in the regulation of endocrine, paracrine, and neurocrine. It is involved in the regulation of growth hormone, adrenocorticotropic hormone, thyroid, mineralocorticoid, and cortisol secretion. These hormones may also serve as a kind of signal linking energy balance regulation, reproduction, stress response, and cardiovascular regulation. Many studies have demonstrated the ability of orexin-A to regulate adrenocortical cells through the MAPK (mitogen-activated protein kinases) pathway. The aim of our study is to investigate the effect of orexin-A on cortisol secretion via the protein 70 ribosomal protein S6 kinase-1 (p70S6K) and eukaryotic translation initiation factor 4E binding proteins (4EBP1) signaling pathway in adrenocortical cells. We reported the first evidence that orexin-A stimulated p70S6K and 4EBP1 in human H295R adrenocortical cells in a concentration and time-dependent manner. 10−6 M orexin-A treatment for 1 hour was the most potent. Our results also indicated that p70S6K and 4EBP1 kinases participated in controlling cortisol secretion via OX1 receptor in H295R cells, which implied important role of p70S6K and 4EBP1 kinases in regulating adrenal function induced by orexin-A.